Role of rootstocks in yield and quality of grapes (Vitis vinifera) under semi-arid tropics of India: a review (Current Horticulture, 2024)
Grape (Vitis vinifera L.) cultivation is gaining importance under tropical and sub-tropical conditions of India by adapting  advance crop techniques. The problems of detoriated soil, poor and shortage of water conditions affecting the grape production  on own rooted vines, which results into use of rootstock in grape cultivation. There are large number of rootstocks available  in grape cultivation according to different production constraints. Rootstock not only helps in withstanding vineyard in  adverse climatic conditions but also help in improving yield and quality of. The rootstock Dogridge became popular among  the grape growers due to its capabilities of overcoming abiotic stresses and better stionic combination. The rootstock suitable  for one variety in a given location may not be suitable for the same variety on other location. Hence, choice of rootstock is  varied among the different cultivars. In a view of better yield and quality of grapes, there should have better stock-scion  compatibility which imparts high vigour into the scion.
Keywords: Rootstock; Semi-arid tropics; Vinryard; Climatic conditions; Abiotic stresses; Stionic combination